Unintentional rewilding: lessons for trophic rewilding from other forms of species introductions - Tanentzap, Andrew J. (Philos Trans R Soc Lond B Biol Sci, 2018)
Trophic rewilding involves adding species into ecosystems to restore extinct, top-down interactions, but limited quantitative data have prevented a systematic attempt to quantify its outcomes. Here, we exploit species introductions that have occurred for purposes other than restoration to inform trophic rewilding. We compiled 51 studies with 158 different responses of lower trophic levels to a species introduction that restored an extinct interaction, whether it intended to do so or not. Unintentional introductions were compared with checklists of extinct animals to identify potential analogues. Using the latest meta-analysis techniques, we found that the few cases of intentional rewilding had similar effects to unintentional rewilding, though there were large taxonomic and geographical biases. We also tested predictions from studies on trophic cascades about the factors that should influence rewilding. Unintentional rewilding was stronger where introduced consumers were non-invasive, but there was no effect of time that compared sites differed in introduction status, latitude or coevolution of responses with a taxonomically related analogue. Our study now shows that rewilding can reinstate extinct trophic interactions and highlights remaining data gaps that need closure to restore ecosystems across larger scales than has been previously possible. This article is part of the theme issue ‘Trophic rewilding: consequences for ecosystems under global change’.